(untitled) - Pahlavan, Kaveh (Hoboken, NJ, 2005)
The authors present the various technical topics in the context of on-going development of specific new systems and services as well as important recent developments in national and international spectrum allocations and standards. Addresses the major segments of wireless technology: cordless and cellular telephony, personal communication services, mobile data networks and wireless local area networks. Particular attention is given to indoor wireless communications. Every chapter concludes with problem sets including computer exercises, questionnaires and traditional homework problems
Keywords: Wireless communication systems,Hệ thống truyền thông không dây